Whole exome sequencing: a customised approach to exploring the genetic basis of musculoskeletal soft tissue injuries - Gibbon, Andrea (Department of Human Biology, 2025)
Several DNA sequence variants have previously been associated with the risk of musculoskeletal soft tissue injuries, suggesting a role for genetics in the aetiology of common sporting injuries such as chronic Achilles tendinopathy (AT) and anterior cruciate ligament (ACL) ruptures. Genetic risk modifiers have primarily been identified using a hypothesis driven candidate gene approach. However, the ability to identify all risk-conferring variants using this approach alone is limited. Therefore, the primary aim of this thesis was to further define the molecular signatures of musculoskeletal soft tissue injuries mapping to specific genomic intervals encoding several structural and regulatory components of the extracellular matrix (ECM). Genes encoding the tenascin-C (TNC) glycoprotein (9q33.1) and the α1 chain of type XXVII collagen (COL27A1, 9q32), as well as matrix metallopeptidase 3 (MMP3, 11q22) and the α1 chain of type I collagen (COL1A1, 17q21.33), have previously been associated with the risk of injury and were therefore prioritised for further interrogation. Previously associated variants within these regions and/or new candidate variants identified by whole exome sequencing (WES) and prioritised through the application of a customised, tiered filtering strategy, were genotyped in several previously recruited, self-identified White Achilles tendon injury and ACL rupture cohorts. The second aim of this study was to determine whether the observed risk-associated signatures in the self-identified White cohorts were similar to those underpinning injury in an ancestrally admixed sample, using ACL ruptures in a South African Coloured cohort as the phenotypic model.